Circulating nucleic acids in plasma and serum: applications in diagnostic techniques for noninvasive prenatal diagnosis - Gahan PB (Dove Medical Press, 2013)
Peter B Gahan Anatomy and Human Sciences Department, King's College London, London Bridge, London, UK Abstract: The analysis of fetal nucleic acids in maternal blood 13 years ago has led to the initiation of noninvasive methods for the early determination of fetal gender, rhesus D status, and a number of aneuploid disorders and hemoglobinopathies. Subsequently, a comparatively large quantity of fetal DNA and RNA has been demonstrated in amniotic fluid as well as small amounts in premature infant saliva. The DNA and RNA in amniotic fluid has permitted an analysis of core transcriptomes, whilst the DNA and RNA in saliva allows the early detection and treatment monitoring of fetal developmental problems. These aspects are discussed together with the methodology and limits of analysis for noninvasive prenatal diagnosis in predictive, preventive, and personalized medicine. Keywords: fetal circulating DNA/RNA, amniotic fluid, saliva, aneuploidy, thalassemias